Adherence to oral hormonal anticancer agents in breast cancer. Issue 3 (June 2023) - Gori, Stefania; Modena, Alessandra; Foglietta, Jennifer; Verzè, Matteo; Inno, Alessandro; Casarin, Alessandra; Russo, Antonio; Nicolis, Fabrizio
There is an increasing trend towards using oral antitumoral agents in oncological patients. Compared to parenteral therapy, oral treatment offers convenience for both the patient and the healthcare system, with similar efficacy. However, the benefit deriving from oral drugs will be obtained only if patients adhere strictly to the treatment. Medical oncologists must therefore seek to optimize patient adherence. Breast cancer patients, particularly, are often treated with oral hormonal anticancer agents. In this review, we summarized evidence about adherence of breast cancer patients to oral hormonal anticancer agents and the consequences of poor compliance, the barriers to oral treatment and strategies to overcome them.